2015
DOI: 10.1007/s11926-015-0543-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Biomarkers in Dermatomyositis

Abstract: Dermatomyositis (DM) is a chronic acquired disorder that affects primarily the muscle and skin. The pathogenesis of DM, as well as methods for monitoring disease activity and predicting response to therapy, are subjects of active research. Studies looking to unveil the pathogenesis of DM have revealed key molecules that are potential biomarkers of disease activity. This article reviews briefly the recently discovered molecules that are candidate immunological biomarkers for diagnosing and monitoring disease ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…However, their relationship to disease activity is variable, especially in DM, IBM, and JDM, resulting in a great need for the development of more specific and sensitive biomarkers. Presently, we understand that innate and adaptive immunity, as well as non-immune muscle-related mechanisms, are involved in IIM pathogenesis 87,88 . Genes and proteins related to immune activation are some of the many targets for new biomarkers in the IIMs.…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their relationship to disease activity is variable, especially in DM, IBM, and JDM, resulting in a great need for the development of more specific and sensitive biomarkers. Presently, we understand that innate and adaptive immunity, as well as non-immune muscle-related mechanisms, are involved in IIM pathogenesis 87,88 . Genes and proteins related to immune activation are some of the many targets for new biomarkers in the IIMs.…”
Section: Biomarkersmentioning
confidence: 99%
“…Cytokines, particularly interleukin-6 (IL-6), are dysregulated in the IIMs. Studies identified IL-6 expression in both immune and muscle cells in muscle tissue 8892 . Serum IL-6 levels are significantly elevated in DM and JDM, and they correlate with disease activity at diagnosis, with ongoing disease changes after varying treatments, and with the presence of ILD.…”
Section: Biomarkersmentioning
confidence: 99%
“…Therefore, there is a strong relationship between chronic inflammation and SLE. The inflammatory response is always accompanied by an increased release of many cytokines and chemokines, which are proven to intensify the immunoreaction and largely contribute to the pathogenesis of SLE (36)(37)(38)(39). In particular, white blood cells (WBCs) are involved in the secretion of the cytokines and chemokines, which in turn activate these WBCs (40,41).…”
Section: ' Discussionmentioning
confidence: 99%
“…The identification of these markers in combination with expanded diagnostic criteria, to include probable JDM for children without rash, would improve early diagnosis and outcomes for children in the future. Further study into the use of blood-borne IL-6, IL-17, IL-23, IFN-β, BAFF, resistin, TLR3 and TLR-7 may emerge as potential biomarkers for the diagnosis of JDM [ 9 ].…”
Section: Discussionmentioning
confidence: 99%